1997
DOI: 10.2307/1387552
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Self-Concept, Ego Defense Mechanisms, and Religiosity Following Seven-Day Vipassana Meditation Retreats

Abstract: To enhance psychological adjustment, Vipassana meditation assists individuals to perceive the transitory nature of the self. Beeauae the consequences of this potentially troubling insight are not well understood, changes in self-concept and ego defense mechanisms of two cohorts (N1= 222, N2 = 216) of young (M = 18.03 years) Thai participants who attended separate seven-day Vipassana meditation retreats and a nontreated control group (N= 281) were compared. Multivariate statistical analysis revealed positive ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 31 publications
0
71
0
1
Order By: Relevance
“…Causal patterns need to be established empirically, via appropriate longitudinal or, ideally, random assignment designs. Research along these lines into the impact of meditation exercises on positive mental states has generated both positive (Emavardhana and Tori 1997) and negative (Shapiro 1992) consequences. It is possible that religious involvement also has more complicated influences than suggested by our correlational results.…”
Section: Discussionmentioning
confidence: 99%
“…Causal patterns need to be established empirically, via appropriate longitudinal or, ideally, random assignment designs. Research along these lines into the impact of meditation exercises on positive mental states has generated both positive (Emavardhana and Tori 1997) and negative (Shapiro 1992) consequences. It is possible that religious involvement also has more complicated influences than suggested by our correlational results.…”
Section: Discussionmentioning
confidence: 99%
“…Given that several studies have found that participants practicing meditation had higher empathy ratings, it is also not surprising that measures of interpersonal functioning and marital satisfaction increased (Tloczynski & Tantriells, 1998). Finally, several studies, most using TM, have suggested that meditation may foster maturation, because meditators tend to score higher on measures of ego, moral and cognitive development, self-actualization, coping skills and defenses, and states and stages of consciousness (C. Alexander & Langer, 1990;Emavardhana & Tori, 1997;Nidich, Ryncarz, Abrams, Orme-Johnson, & Wallace, 1983;Travis et al, 2004).…”
Section: Positive Well-beingmentioning
confidence: 99%
“…Researchers have reported relationships between meditation and adjustment to college life (Tloczynski and Tantriella 1998), recovery from depression (Ma and Teasdale 2004), self-esteem (Emavardhana and Tori 1997), self-actualization (Alexander et al 1991), moral maturity (Nidich et al 1983), and happiness (Smith et al 1995).…”
Section: Mindfulness Meditation and Quality Of Lifementioning
confidence: 99%